2015
DOI: 10.1007/s13311-014-0312-z
|View full text |Cite
|
Sign up to set email alerts
|

Biometals and Their Therapeutic Implications in Alzheimer's Disease

Abstract: No disease modifying therapy exists for Alzheimer's disease (AD). The growing burden of this disease to our society necessitates continued investment in drug development. Over the last decade, multiple phase 3 clinical trials testing drugs that were designed to target established disease mechanisms of AD have all failed to benefit patients. There is, therefore, a need for new treatment strategies. Changes to the transition metals, zinc, copper, and iron, in AD impact on the molecular mechanisms of disease, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 226 publications
1
92
0
1
Order By: Relevance
“…In AD pathology, metals such as iron, copper, and zinc interact with Aβ [28]. APP translation is promoted by iron [29,30], and we observed increased APP levels in Aβ-injected mice (Figs.…”
Section: Increased Hippocampal Iron Induced By Aβmentioning
confidence: 65%
See 1 more Smart Citation
“…In AD pathology, metals such as iron, copper, and zinc interact with Aβ [28]. APP translation is promoted by iron [29,30], and we observed increased APP levels in Aβ-injected mice (Figs.…”
Section: Increased Hippocampal Iron Induced By Aβmentioning
confidence: 65%
“…We found that one of the persistent effects of Aβ intoxication was increased local iron levels (Fig. 8), which is also pathology of AD [28,39]. Lowering brain iron has been shown to reduce memory deficits and neuronal loss in AD animal models and in a clinical trial [11,14,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 79%
“…52,102,103,104 Despite the neurotoxicity in mice that our studies have elaborated, clinical lithium pharmacotherapy has predominantly neurotrophic benefits in the treatment of bipolar disorder. It is an intriguing hypothesis to consider that these benefits might be related to the correction of iron deficiency in certain brain regions.…”
Section: Discussionmentioning
confidence: 98%
“…While the relation of copper and zinc to AD and the APP protein has proven quite solid, evidence supporting a link between iron and AD has taken much longer to emerge [69]. Elevated brain iron has been reported in patients with AD [70,71].…”
Section: Iron In Alzheimer's Diseasementioning
confidence: 99%